Social Construction of FOMO (Fear of Missing Out) for Psychological Well-Being among Generation Z - Elok Azimatuz Zahroh; Muhamad Furqon (Al-Qalam Institute, 2025)
The Fear of Missing Out (FOMO) phenomenon has become increasingly prominent among Generation Z as social media use has expanded, raising concerns about psychological well-being. This study aims to explain how FOMO is socially constructed through digital interactions and how it influences the mental health of Generation Z. Using a qualitative case-study approach, data were collected from Generation Z individuals, social observers, and psychologists through in-depth interviews and observations of social media behavior. The findings reveal that FOMO emerges primarily through social comparison, constant digital visibility, and perceived pressure to remain socially relevant. These conditions contribute to heightened anxiety, emotional distress, and reduced life satisfaction. This study offers a novel contribution by conceptualizing FOMO as a socially constructed experience rather than solely an individual psychological response. The results highlight the importance of social awareness and critical engagement with digital content. Practically, the findings suggest the need for media literacy education, emotional regulation strategies, and strengthened social support to mitigate the adverse psychological effects of FOMO among Generation Z.